Neuro fuzzy classification and detection technique for bioinformatics problems [electonic resource] - 177495 Moh, Thomas Shan Yau (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2006